Dual antibody status predicts sustained remission in patients with rheumatoid arthritis - Praveen Pratap Jadhav; Jaya Dilip Avhad; Mahendra Mahajan; Asmanaz Mehemud Patel; Hemant Ramchandra Gavli; Janhavee Praveen Jadhav; Vaibhav Khandelwal (Indian Journal of Rheumatology)
Background: Rheumatoid factor (RF) and anti-cyclic citrullinated protein (ACCP) estimation have been used to improve the diagnosis of rheumatoid arthritis (RA). However, their role in prognostication of RA, individually and in combination, is not well studied. This is, especially, true for Indian patients. Methods: Consecutive 945 patients who had their RF and ACCP determined were included in the study. They were followed up for 3 months to 24 months. Swollen joint count, erythrocyte sedimentation rate, disease activity score 28 (DAS 28), and Indian version of Health Assessment Questionnaire (HAQ) were checked during each visit. They were treated with conventional disease-modifying agents (DMARDS). Results: At presentation, patients with both antibodies positive had the most severe disease, while those with both antibodies negative had the least severe disease. Among discordant antibody status (one antibody positive and the other negative), patients with ACCP positivity presented with higher disease activity than with RF positivity. Patients with dual antibody positivity were much less likely to be in remission than with both negative antibodies. The percentage of patients in remission were 34.2, 29.5, 32.4, and 24.7, respectively, for RF−/ACCP−, ACCP+/RF−, ACCP−/RF+, and ACCP+/RF+. Both, ACCP (odds ratio [OR]: 0.76; 95% confidence interval [CI]: 0.74–0.78) and RF (OR: 0.68; 95% CI: 0.66–0.70) positivity were associated with lower odds of sustained remission (P < 0.05). Conclusion: Dual antibody-positive status at presentation carries poor prognosis, higher disease activity, higher HAQ score, and lesser chance of remission in RA patients with conventional treatment. Patients with both antibodies negative status had the best prognosis. Although patients with discordant antibody status had an intermediate prognosis, the ones with ACCP had higher disease activity at follow-up.